2021
DOI: 10.1021/acs.jafc.1c05674
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dihydropteroate Synthase-Based Fluorescence Polarization Assay for Detection of Sulfonamides and Studying Its Recognition Mechanism

Abstract: In this study, the dihydropteroate synthase of Staphylococcus aureus was obtained, and its recognition mechanisms for 31 sulfonamide drugs were studied. Results showed that their core structure matched well with the binding pocket of paraaminobenzoic acid, and all the sulfonamide side chains were out of the binding pocket. Hydrogen bonds and hydrophobic interactions were the main intermolecular forces, and the key amino acids were Gly171 and Lys203. The binding sites in sulfonamide molecules were mainly around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…For a comparison to related methods, the main results of some previously reported conventional immunoassays and DHPS-based assays are summarized in Table . First, the operation steps of the present method were the same as those of the direct competitive methods ,,,, and fewer than those of the indirect competitive methods, ,,, but more than those of the fluorescence polarization methods. ,, Second, the assay time (from adding sample) of the present method was comparable to or shorter than ,,,,,, that of the indirect competitive and direct competitive methods, but longer than the fluorescence polarization methods. ,, Third, the sensitivity of the present method was higher than all of those methods, even the fluorescence polarization methods and the chemiluminescence method. Fourth, the detection spectrum of the present method was broader than all of those methods.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…For a comparison to related methods, the main results of some previously reported conventional immunoassays and DHPS-based assays are summarized in Table . First, the operation steps of the present method were the same as those of the direct competitive methods ,,,, and fewer than those of the indirect competitive methods, ,,, but more than those of the fluorescence polarization methods. ,, Second, the assay time (from adding sample) of the present method was comparable to or shorter than ,,,,,, that of the indirect competitive and direct competitive methods, but longer than the fluorescence polarization methods. ,, Third, the sensitivity of the present method was higher than all of those methods, even the fluorescence polarization methods and the chemiluminescence method. Fourth, the detection spectrum of the present method was broader than all of those methods.…”
Section: Resultsmentioning
confidence: 80%
“…For development of a signal-amplified ELISA, SZ was coupled with HRP, sHRP, and bHRP, individually, to prepare three enzyme-labeled conjugates (HRP-SZ, sHRP-SZ, and bHRP-SZ) by using the glutaraldehyde method. In our recent report, the molecular docking showed that DHPS could interact with the aromatic primary amine, phenyl ring, and −SO 2 N– part in SAs molecules . So this conjugate synthesis method would not influence the DHPS bindings for the three conjugates, even if the aromatic primary amine in the SZ molecule was occupied.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations